Mother's Influence Child’s On the Speech Development in Kenya - Sichari, Manson (Archives of Business Research, 2016)
Mothers have key roles in their children’s speech development. Sibling a child true love is an essential step in speech development. Simply talking to a child and getting a conversation going by means of emotional expression, gestures and sounds equally important while doing this, it is necessarily to follow the child’s lead signs, expressions, gestures, emotions, praising and appreciating what the child’s manages to do and helping him or her to focus on his or her attention, thus sharing the child’s experiences. Mothers therefore, play a big role in helping their children to learn rules, limits values and more importantly develop their speech in a natural manner.